Answer:
f = 3 1/2
Step-by-step explanation:
f = 2t - 3f Substitute 7 for t
f = 2(7) - 3f Multiply
f = 14 - 3f
+3f + 3f Add 3f to both sides
4f = 14 Divide both sides by 4
f = 3 1/2
If this answer is correct, please make me Brainliest!
7g - 6 = -20
Add 6 to both sides
7g = -14
Divide both sides by 7
g = -2
answer: g = -2
Answer:
Simplifying the expression we get
Step-by-step explanation:
We need to simplify the expression
Solving:
Applying exponent rule:
Factors of
Factors of
Replacing terms with factors
Using exponent rule:
Using exponent rule:
Now using exponent rule:
So, simplifying the expression we get
4x-4>20
Step 1: Add four to both sides
4x-4+4>20+4
4x>24
Step 2: Divide both sides by 4
4x divided by 4 and 24 divided by 4
Answer: x>6
Kahal accidentally subtracted instead of adding. He made a mistake in step 2.